The Effect Of Profitability, Tunneling Incentive And Deferred Tax On Tax Aggressiveness - Andrenossa, Glenn; Octaviani, Theresia; Mentari, Theresia (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
The largest source of state budget revenue in Indonesia is from tax revenue. Tax is an important factor in the development of a country. But on the one hand, companies try to minimize their tax burden, by taking tax aggressiveness. Tax aggressiveness is one of the strategies carried out by corporate taxpayers in avoiding tax burdens, by reducing tax burden reporting or by saving tax reporting. This is based on the company's desire to obtain optimal profits. This study aims to analyse the factors that influence tax aggressiveness actions taken by companies. These factors are profitability, tunnelling incentive, and deferred tax. This research is a quantitative study using a sample of 22 mining sub-sector companies listed on the Indonesia Stock Exchange, with an observation year of five years, 2018-2022. The data analysis technique used is multiple linear regression analysis. The results showed that profitability and tunnelling incentive had no effect on tax aggressiveness. Meanwhile, deferred tax has a positive but insignificant effect on tax aggressiveness